Moebjergarctus clarionclippertonensis, a new abyssal tardigrade (Arthrotardigrada, Halechiniscidae, Euclavarctinae) from the Clarion-Clipperton Fracture Zone, North-East Pacific - Bai, Lifen; Wang, Xiaogu; Zhou, Yadong; Lin, Shiquan; Meng, Fanxu; Fontoura, Paulo (Zootaxa, 2020)
A new marine tardigrade, Moebjergarctus clarionclippertonensis sp. nov., is described based on specimens collected from a manganese nodule area in the Clarion-Clipperton Fracture Zone of the abyssal North-eastern Pacific. The new species is a member of the bathyal/abyssal subfamily Euclavarctinae Renaud-Mornant, 1983. Within the Euclavarctinae, the genus Moebjergarctus Bussau, 1992, with only one described species, M. manganis Bussau, 1992, is characterised by simple claws, club-shaped and anteriorly bent primary clavae, well-developed spherical secondary clavae and cephalic cirri separated into three parts: short cirrophore, long and annulated scapus, and a short flagellum. Moebjergarctus clarionclippertonensis sp. nov. can be distinguished from M. manganis by the morphology of cephalic cirri which have scapi annulated only in the proximal part and by the presence of a caudodorsal bulge covered by a crescent-shaped cuticular thickening.